Chest pain following the use of fluvoxamine in depression. (June 2019) - Pang, Tamara; Gudi, Alakananda
Selective serotonin reuptake inhibitors are considered to be the drug of choice in patients with major depression and cardiovascular disease. Fluvoxamine in particular has been shown to be safe for use in patients with cardiovascular disease. We report a case of chest pain precipitated by fluvoxamine in an elderly lady with a known history of cardiovascular disease. This highlights the need for psychiatrists to be aware of chest pain as a potential side effect of fluvoxamine in their patients.